The surgical treatment of traumatic rupture of aortic valve and atrial septum after blunt chest trauma: literature review and presentation of a rare case - Arruda Filho,Mauro Barbosa (2003)
The case of a 49-year-old man who suffered a car accident responsible for several chest injuries including fractures of the left ribs, large subcutaneous emphysema and left hemopneumothorax arrived in shock in the Emergency Room of the Real Hospital Português de Beneficência in Pernambuco (RHPBPE). He was hospitalized for 30 days including some time in the intensive care unit and but did not show signs of diastolic murmur or heart failure. He was submitted to an echocardiography examination that diagnosed slight aortic incompetence, good left ventricular function and was discharged after clinical improvement. Three months later he started to feel symptoms of heart failure and returned to cardiac Emergency Room of the same Hospital. He repeated transthoracic and transesophageal echocardiography examinations presenting severe aortic incompetence due to leaflet disruption, rupture of atrial septum with enlargement of the right cardiac chambers and poor left ventricular function. He underwent surgical treatment of these lesions, with direct approach of the atrial septum and the aortic valve was replaced with a mechanical prosthesis, with a good result.